Subseasonal Great Plains Rainfall via Remote Extratropical Teleconnections: Regional Application of Theory‐Guided Causal Networks. Issue 5 (23rd February 2023) - Malloy, Kelsey; Kirtman, Ben P.
Abstract: Long‐range U.S. summer rainfall prediction skill is low. Monsoon variability, especially over the West North Pacific Monsoon (WNPM) and/or East Asian Monsoon (EAM) region, can influence U.S. Great Plains hydroclimate variability via a forced Rossby wave response. Here, we explored subseasonal monsoon variability as a source of predictability for Great Plains rainfall. The boreal summer intraseasonal oscillation (BSISO) is related to Great Plains convection and Great Plains low‐level jet (LLJ) anomalies as well as a cross‐Pacific wave train. Using a causal effect network, we found that the time between BSISO‐related geopotential height anomalies and Great Plains rainfall anomalies is about 2 weeks; therefore, BSISO convection may be a valuable forecast of opportunity for subseasonal prediction of Great Plains convection anomalies. More specifically, causal link patterns/maps revealed that the above‐normal weekly EAM rainfall, rather than WNPM rainfall or general geopotential height activity over the East Asia, was causally linked to Great Plains LLJ strengthening and active Great Plains convection the following week. Plain Language Summary: Forecasting U.S. summer rainfall out past ∼7–10 days, considered the subseasonal timescale, is a challenge. However, there are times when subseasonal forecast skill is relatively higher due to propagating atmospheric waves from remote climate events. The West North Pacific Monsoon (WNPM) and East Asian Monsoon (EAM) can provide a remote influence via their related heating triggering atmospheric waves. Using an algorithm that effectively identifies and quantifies cause‐and‐effect relationships, we constructed a network that connects EAM rainfall and Great Plains rainfall via these atmospheric waves. We found that above‐normal EAM rainfall, rather than WNPM rainfall or general atmospheric wave activity over the East Asia, was causally linked to active Great Plains convection the following week. Therefore, monsoon variability, especially over the EAM region, might be a valuable source of subseasonal predictability for U.S. summer rainfall. Key Points: Subseasonal monsoon variability is linked to rainfall signals over U.S. Great Plains and its associated dynamical drivers A cause‐and‐effect algorithm verified a pathway from regional monsoon rainfall to Great Plains rainfall, which takes approximately 2 weeks Weekly East Asian monsoon rainfall is causally linked to Rossby wave excitation and active Great Plains convection about 1 week later